2021
DOI: 10.1177/11297298211039633
|View full text |Cite
|
Sign up to set email alerts
|

Tunneled femoral dialysis catheter: Practical pointers

Abstract: One of the most challenging aspects of providing end-stage kidney disease care is to achieve adequate long-term access to the bloodstream to support hemodialysis (HD) therapy. Although upper extremity arteriovenous fistula remains the vascular access of choice for patients on HD, complications such as central venous stenosis, access thrombosis, or exhaustion of suitable access sites in the upper extremity, ultimately result in pursuing vascular access creation in the lower extremity. The current review focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been suggested that TDC with a femoral approach and tip placement in the right atrium may potentially inhibit the success of achieving adequate blood flow and potentially promote the development of long fibrin sheaths leading to shorter patency of the access. 18 In a prospective observational study, TDC tips with a femoral approach placed at the upper third of the IVC or the junction of the IVC and right atrium resulted in 6-and 12-month primary patency rates of 66.6% AE 12.6% and 54.2% AE 16.6%, respectively. 19 While other studies have shown lower primary patency rates at 6 months ranging from 55 to less than 20% when placed in the lower IVC, though a direct comparison between these studies is not easily made.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that TDC with a femoral approach and tip placement in the right atrium may potentially inhibit the success of achieving adequate blood flow and potentially promote the development of long fibrin sheaths leading to shorter patency of the access. 18 In a prospective observational study, TDC tips with a femoral approach placed at the upper third of the IVC or the junction of the IVC and right atrium resulted in 6-and 12-month primary patency rates of 66.6% AE 12.6% and 54.2% AE 16.6%, respectively. 19 While other studies have shown lower primary patency rates at 6 months ranging from 55 to less than 20% when placed in the lower IVC, though a direct comparison between these studies is not easily made.…”
Section: Discussionmentioning
confidence: 98%